Slovene Nominal Diminutives and their English Equivalents: A Comparison - Eva Sicherl (ELOPE, 2012)
A contrastive analysis of nominal diminutives in Slovene and English clearly shows that diminutive formation and use of diminutives in Slovene is tied to the morphological characteristics of nouns and, consequently, their morphological–lexemic features, whereas the focus of diminutive formation and use in English remains bound to the syntactic use, or rather, the respective syntactico–semantic use of a given lexeme. In all languages, diminutiveness is a basic meaning– forming element, which can, however, be realized predominantly morphologically, as is the case in Slovene, or predominantly syntactically, as is the case in English. As a meaning–forming element it also plays a crucial role in the development of terminology – in this case the diminutive as language metaphor gains semantic independence and becomes a technical term.